Removing cross-border capacity bottlenecks in the European natural gas market: A proposed merchant-regulatory mechanism - Anne Neumann; Juan Rosellón; Hannes Weigt (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We propose a merchant-regulatory framework to promote investment in the European natural gas network infrastructure based on a price cap over two-part tariffs. As suggested by Vogelsang (2001) and Hogan et al. (2010), a profit maximizing network operator facing this regulatory constraint will intertemporally rebalance the variable and fixed part of its two-part tariff so as to expand the congested pipelines, and converge to the Ramsey-Boiteaux equilibrium. We confirm this with actual data from the European natural gas market by comparing the bi-level price-cap model with a base case, a no-regulation case, and a welfare benchmark case, and by performing sensitivity analyses. In all cases, the incentive model is the best decentralized regulatory alternative that efficiently develops the European pipeline system.
Keywords: 330; regulation; transportation network; investment; Erdgasmarkt; Gasleitungstransport; Regulierung; Ökonomischer Anreiz; Europa